2016
DOI: 10.1159/000447928
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia with Persistent Elevated Urinary Fractional Uric Acid Excretion: Evidence for Proximal Tubular Injury?

Abstract: Background/Aims: Hyponatremia associated with high urinary fractional excretion of uric acid which persists after serum sodium is corrected is the cardinal feature of salt losing nephropathy (SLN). We hypothesize that low grade proximal tubular injury is present in SLN because the proximal tubule is the main site of uric acid and sodium transport. Methods: Five subjects with SLN were compared to four subjects with recurrent hyponatremia and three healthy individuals. Urinary NGAL (neutrophil gelatinase associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…In turn, we have shown in a model of diabetic nephropathy that fructokinase-mediated tubular injury is also associated with worse albuminuria and glomerular injury (22), suggesting this might represent the link between vasopressin and glomerular injury. Consistent with this cross talk, we have recently reported evidence for tubular injury in patients with chronic hyponatremia, and in these patients urinary fructose levels are elevated (24). In addition, fructose also stimulates vasopressin release (11,35), thereby leading to a positive feedback system (18).…”
Section: Discussionsupporting
confidence: 62%
“…In turn, we have shown in a model of diabetic nephropathy that fructokinase-mediated tubular injury is also associated with worse albuminuria and glomerular injury (22), suggesting this might represent the link between vasopressin and glomerular injury. Consistent with this cross talk, we have recently reported evidence for tubular injury in patients with chronic hyponatremia, and in these patients urinary fructose levels are elevated (24). In addition, fructose also stimulates vasopressin release (11,35), thereby leading to a positive feedback system (18).…”
Section: Discussionsupporting
confidence: 62%
“…-Finally, the association between high FE urate and enhanced sodium excretion over time may comfort previous studies that hypothesized a defect in sodium transport in the proximal tubule [4]. In this respect, Maesaka et al first suggested the increased excretion fraction of solutes exclusively transported in the proximal tubule such as lithium, urate and eventually phosphate in patients with SWS [15][16][17]. Moreover, proximal renal tubular dysfunction has recently been described in brain-damaged patients [18].…”
Section: Discussionmentioning
confidence: 75%
“…Basic biochemistry parameters (including lipid profiles, fasting serum glucose, serum creatinine, serum uric acid, urinary creatinine and urinary uric acid) were analysed using a Hitachi 7600-110 Chemistry Autoanalyzer (Hitachi, Ltd., Tokyo, Japan). FEUA was calculated as the ratio of urinary uric acid in umol/L to serum uric acid in umol/L divided by the ratio of urinary creatinine in umol/L to serum creatinine in umol/L [15]. Estimated glomerular filtration rate (eGFR) was calculated using the Chronic Kidney Disease Epidemiology Collaboration equation as shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%